ANOTHER ALTERNATIVE IN TEACHING ENGLISH: A Theoretical Perspective - Ghofur, Abd. (OKARA: Jurnal Bahasa dan Sastra, 2013)
The objective of this written, actually, going to show that literature is a good way to deliver a language learning, in this case leaners could comprehend the language itself by literature as medias of teaching. In this case, of one the literature that could use as a technique to teach language, especially English is drama. Drama can foster skills such as reading, writing, speaking and listening by creating a suitable context. Drama is a powerfull language teaching tool that involves all of the students interactively all of the class period. Drama can also provide the means for connecting studentsâ€™ emotions and cognition as it enables students to take risk with language and experience the connection between thought and action. Teaching English as a foreign language inevitably involves a balance between receptive and productive skills; here drama can effectively deal with this requirement. Through drama, a class will address, practice and integrate reading, writing, speaking and listening. Drama also fosters and maintains studentsâ€™ motivation, by providing an atmosphere which is full of fun and entertainment. In so doing, it engages feelings and attention and enriches the learners’ experience of the language.